Pelatihan Penggunaan Aplikasi Trello Sebagai Project Management Pada Raz Hotel & Convention Medan - Fahlevi, Muhammad Reza; Putri, Dini Ridha Dwiki; Nasution, Farhan Syabandi (LPPM Universitas Potensi Utama, 2022)
Trello is a management application that can help get things done, especially those related to teamwork. By using this Trello application, it can make work easier with colleagues who are involved with each other. Trello will know what work is being done, who is doing it, and how far the progress is. Trello can be used by project managers because it can organize multiple tasks to make them more organized. Staff performance is the result of work in carrying out tasks in accordance with the responsibilities assigned to all staff, carrying out work according to the work table, and having skills that support the work. The purpose of this community service is to provide an understanding to the staff of Raz Hotel & Convention Medan on the creation of management projects that are implemented into the Trello application so that staff can manage their work clearly and neatly and provide explanations regarding technological developments and the ability of Raz Hotel & Convention Medan staff in managing projects and job desks in the Trello application. By utilizing the Trello application, Raz Hotel & Convention Medan staff can manage their work so that their main job desk can be structured and scheduled clearly and neatly. With the features available in Trello, HRD and HR Manager of Raz Hotel & Convention Medan can find out how far the progress of each HR department's work and HR Manager can also find out which staff in each department are late or not doing their work.